1982
DOI: 10.1063/1.93060
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-oxygen complexes as nuclei for the precipitation of oxygen in Czochralski silicon

Abstract: Enhanced photoluminescence detection of oxygen in silicon crystal by formation of a carbon-oxygen complex through carbon implantation and electron irradiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…lb. A weak band is also observed at the same position (1012.5 cm-') at LHT; this band was also reported without comment by Oerhlein et al (11). There is a correlation between these bands and the Oi concentration but not with the carbon or boron concentration.…”
Section: Resultssupporting
confidence: 81%
“…lb. A weak band is also observed at the same position (1012.5 cm-') at LHT; this band was also reported without comment by Oerhlein et al (11). There is a correlation between these bands and the Oi concentration but not with the carbon or boron concentration.…”
Section: Resultssupporting
confidence: 81%
“…Therefore, it indicates that Ge-doping in Cz Si can enhance the formation of oxygen precipitation during crystal growth, i.e., the generation of as-grown oxygen precipitation. It is well accepted that the homogenous nucleation mechanism for oxygen precipitation predominates during high temperature annealing (T4900 1C) [23], that is, the super-saturation of oxygen dominates the precipitation in crystals. So as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The OPM observations show that denuded zones were formed at the subsurface region in all of these wafers, regardless of the carbon concentrations. It has been shown that carbonoxygen complexes can act as nucleation centers for the precipitation of oxygen (30). However, during the first step, 1050~ annealing, the interstitial oxygen atoms diffuse out of the wafer surface and lower the oxygen concentration in the subsurface region to an undersaturated level, and oxygen precipitation at the subsurface region will not occur, despite the high concentration of carbon atoms existing in this region.…”
Section: Initial Carbon Concentrationmentioning
confidence: 99%